Pengaruh Islamic Attributes, Aksesibilitas dan Citra Destinasi Terhadap Minat Berkunjung Wisatawan di Kabupaten Bandung Barat - Karsana, Rifda Milati Hanifa (Educationist: Journal of Educational and Cultural Studies, 2023)
The aim of this research is to determine the influence of Islamic attributes, accessibility and destination image on tourists' interest in visiting tourist attractions in West Bandung Regency. This research is part of quantitative research using a survey method, namely through the distribution of Google forms. Sampling in this research used a purposive sampling technique, the research sample was 170 respondents. The analysis in this research uses the structural equation modeling method and is processed using SmartPLS 3.0 software. The results of this research, namely the variables of Islamic attributes, accessibility and destination image, were proven to have a positive and significant influence on tourists' interest in visiting tourist attractions in West Bandung Regency. The Islamic attribute variable is a factor that has a big influence on tourists' interest in visiting.